Fuel ethanol production using novel carbon sources and fermentation medium optimization with response surface methodology - Wu, Weihua (International Journal of Agricultural and Biological Engineering, 2013)
In this study, ethanol production abilities of the novel carbon sources: sodium and calcium gluconate in different minimal and rich media were compared with glucose using Escherichia coli KO11. The strain produced higher ethanol yield in the rich medium Luria-Bertani (LB) than the other two minimal media: corn steep liquor (CSL) and M9 for two substrates (sodium and calcium gluconate). Additionally, higher ethanol yields were achieved when the strain was grown in LB and M9 medium with calcium gluconate than sodium gluconate, while the ethanol yields were similar when both sodium and calcium gluconate were added into CSL medium respectively. Response surface methodology was used to optimize the fermentation medium components for enhancing ethanol production using strain E. coli KO11 in CSL medium with calcium gluconate as the substrate in batch culture. The concentration of the potassium phosphate buffer is the only significant factor among five factors considered. A quadratic model was developed to describe the relationship between ethanol production and the factors. The optimal conditions predicted for five factors were 14.38 g/L CSL, 0.0398 g/L FeCl3•6H2O, 1.12 g/L MgSO4•6H2O, 15.41 g/L (NH4)2SO4, and 1.58/1.26 g/L KH2PO4/K2HPO4 (2:1 molar ratio). The highest ethanol concentration under optimal conditions was 31.5 g/L, which was 5.6 g/L higher than that from the same fermentation concentration of calcium gluconate in LB media. The high correlation between the predicted and experimental values confirmed the validity of the model.